The Development of Google Forms-Based Student Worksheets for Learning Vocabulary and Grammar for Seventh-Grade Students of Madrasah Tsanawiyah - Eneng Titi Winarti; Erta Mahyudin; N. Lalah Alawiyah (Penerbit Minhaj Pustaka, 2026)
يهدف هذا البحث إلى إنتاج مادة التمرينات لتعليم المفردات والتراكيب بتطبيق جوجل فورمز في المدرسة الثانوية الإسلامية الحكومية ٣ جيليجون، ووصف إجراءات التعلم للمفردات والتركيب باستخدام التمرينات بتطبيق جوجل فورمز، وتطويرها، وتقييم فعاليتها. يستخدم هذا البحث منهج البحث والتطوير (R&D) بنموذج التطوير ADDIE منهج الأساليب المختلطة. تُظهر نتائج البحث أن التمرينات بتطبيق جوجل فورمز فعالة في استخدامها كوسيلة للممارسة المستقلة بعد التعلم في الفصل. يساهم توظيف هذه الوسيلة في معالجة أوجه القصور في التمرينات التقليدي التي تتسم بالرتابة وقلة المرونة، خاصة في المدارس التي تقيّد استخدام الأجهزة الإلكترونية في الفصل. توفر التمرينات بتطبيق جوجل فورمز فرصةً للطلاب للتمرّن على المفردات والتراكيب بشكل مستقل خارج الفصل لأنها سهلة الوصول، كما أنها تسهل على المدرّس عملية تقديم التمرينات وتقييمها. تظهر نتائج تعلم الطلاب تحسناً بعد استخدام هذا التمرينات. وبناء على ذلك، يمكن اعتبار التمرينات بتطبيق جوجل فورمز بديلا مناسبا وفعالا للممارسة المستقلة في تعليم المفردات والتراكيب. Abstract This study aims to develop Google Forms-based student worksheets for learning mufrodat and tarkib at State Islamic Junior High School 3 Cilegon, describe the procedures for their implementation in the learning process, develop worksheets based on Google Forms, and assess their effectiveness. This study used the R&D (Research and Development) method with the ADDIE development model and a mixed-methods approach. Research findings show that Google Forms-based worksheets are effective as a medium for independent practice after classroom learning. The use of this medium can overcome the limitations of conventional worksheets, which are monotonous and inflexible, especially in schools that restrict the use of electronic devices in the classroom. Google Forms-based worksheets provide students with the opportunity to practice mufrodat and tarkib independently outside of class because they are easily accessible and make it easier for teachers to assign and assess exercises. Student learning outcomes show improvement after using worksheets. Thus, Google Forms-based worksheets can be a relevant and effective alternative medium for independent practice in mufrodat and tarkib learning.